The value of a head turn in neurolocalization - Aran Nagendran; Roberto José López; Anna Suñol; Josep Brocal; Rita Gonçalves (Journal of Veterinary Internal Medicine, 2024)
Abstract Background A head turn is a clinically relevant abnormality identified on neurological examination and historically has been an isolated or concomitant sign of ipsilateral forebrain dysfunction. Experimental studies in quadrupedal mammals suggest that changes in head posture may be identified as originating in other parts of the central nervous system (CNS). Objectives To identify whether other locations within the CNS could give rise to a head turn and whether the head turn identified is isolated or concomitant with other deviations in head and body posture. Animals Forty‐nine client‐owned dogs with a presentation of a head turn, from 6 veterinary referral centers. Methods Multicenter observational prospective study including dogs with photographic evidence of a head turn, full neurological examination, and advanced imaging. Results Of the population, 15/49 had head turn only, 9/49 had head turn and head tilt only, 12/49 had head turn and body turn only, and 13/49 had head turn, head tilt, and body turn. Nearly all dogs with forebrain disease (23/24), and, all with brainstem and cerebellar disease, had an ipsilateral head turn and body turn (if present). In the cerebellar group, all head tilts were contralateral to the lesion location. In the cervical spinal cord group, all head turns, body turns and head tilts were contralateral to the lesion location. Conclusion A head turn, although most likely associated with, is not exclusively seen with forebrain disease. Certain combinations of head turn, head tilt and body turn suggest a neurolocalization other than the forebrain, with appropriate classification needed.